(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
The author proposes a reflection on the social changes that led to the emergence of a movement that advocates for black representation in the performing arts field in recent years. Based on an analysis of some of the ways in which the black body is represented in the scene, especially in the play Entrevista com Stela do Patrocínio, this article also aims to reflect on the political and social implications caused by the presence and the absence of the black body in the contemporary theater scene.